Over a million students use our free study notes to help them with their homework
23x - 1 = 3log2(23x-1) = log2(3)3x - 1 = log2(3)3x = 1 + log2(3)x = 1/3 + 1/3log2(...
Apply the double angle formula to cos2x to yield the requested result.cos2x = 2cos^2(x) - 1Spot that the question asks us to prove the value of cos^2(x) when integrated, and that we can move t...
First, manoeuvre variables so that we can integrate the equation.1/(x-6)^(1/2) dx = -2 dtIntegrate the equation and add the constant.2(x-6)^(1/2) = -2t +cSolve for t.t = -(x-...
Using the substitution u = sec(z)=> du = sec(z)tan(z) dz.So, the integral ∫ y dz = ∫ sec(z)tan(z)/sqrt(sec(z)) dz=> ∫ y dz = ∫ 1/sqrt(u) du = 2sqrt(u) + C = 2sqrt(sec(z)) + C.
First, you will need to differentiate the function with respect to x. Finding dy/dx.For polynomials, this is done by taking one away from the old power and multiplying the coefficient by the old power and...
←
218
219
220
221
222
→
Internet Safety
Payment Security
Cyber
Essentials